O gestor da escola pública da região noroeste do Rio Grande do Sul: políticas educacionais na perspectiva da Inclusão - Lepke, Sonize (My University, 2019)
The present thesis analyzes how public school administrators in the Northwest region of the State of Rio Grande do Sul employed and interpreted inclusive education policies. Administrators of two state schools (high school) were the subjects of this case study. We adopted a pluralist epistemological perspective based on approaches along the Theory of Policy Enactments, by Ball, Maguire, and Braun (2016). Semi-structured interviews conducted alongside school administrators, the Field Journal's notes, and Political-Pedagogical Projects (PPP) of the schools were all used as data for the present study. Conclusions were drawn from the categories and subcategories that emerged following the Textual Discourse Analysis (TDA) developed by Moraes and Galiazzi (2007), organized according to the Theory of Action. We concluded that: a) the national and international debates promote schools that accommodate all students. From this perspective, several countries are pressured to develop public policies that contribute to the effectiveness of inclusive education systems and that, at the same time, meet the interests of the neoliberal economy; b) In the last two decades, the federal government of Brazil has developed policies, decrees, legislation, opinions, and resolutions that draw from international organizations. However, the government of Rio Grande do Sul has developed several documents to instruct school managers in this regard; c)school administrators are unaware of, omit or neglect inclusive educational policies, attributing the education of students with disabilities, pervasive developmental disorders, and intellectual giftedness solely to Special Schools; d) the Sala de Recursos Multifuncionais (SRM) and Escola Acessível (EA) programs are not referred to as programs that integrate inclusive educational policies; e) the school administrator is responsible for the human and financial resources that make up a democratic school system. Due to the lack of resources and legal support, Inclusive Education is threatened. The inclusive education policies are a result of the tension of international mechanisms and the organization of civil society. As for practice (school), the policies guided school administrators who, in the process of interpreting, spuriously employed its recommendations and omitted or ignored crucial aspects that sought to ensure access and stay of students targeted by Special Education in regular school.
Esta tese propõe analisar como as políticas educacionais, na perspectiva da inclusão, orientam os gestores de escolas públicas da região Noroeste do Estado do Rio Grande do Sul e são por eles interpretadas. A pesquisa, caracterizada como estudo de caso, tem como sujeitos os gestores de duas escolas da rede estadual de ensino. O referencial teórico adota uma perspectiva epistemológica pluralista fundamentada nas aproximações com a Teoria da Atuação em Políticas, de Ball, Maguire e Braun (2016). A construção dos dados, a partir das fontes de evidências, baseia-se nas entrevistas semiestruturadas realizadas com os gestores das escolas, no Diário de Campo composto por registros, e nos Projetos Político-Pedagógicos (PPP) das escolas. As conclusões são apresentadas a partir das categorias e subcategorias que emergiram da Análise Textual Discursiva (ATD), de Moraes e Galiazzi (2007), organizadas segundo as dimensões contextuais da Teoria da Atuação. As principais conclusões são: a) os debates nacionais e internacionais apontam para a organização de escolas que acolham todos os estudantes. A partir dessa definição os diferentes países passaram a ser pressionados a elaborar políticas públicas que colaborem com a efetivação de sistemas de ensino inclusivos e, ao mesmo tempo, atendam a interesses da economia neoliberal; b) O governo federal elaborou, nas duas últimas décadas, políticas, decretos, pareceres e resoluções, observando as orientações dos organismos internacionais. O governo do Estado do Rio Grande do Sul, entretanto, concebeu poucos documentos para orientar os gestores escolares nesse aspecto; c) os gestores escolares desconhecem, omitem ou negligenciam as políticas educacionais na perspectiva da inclusão e tendem a responsabilizar as Escolas Especiais pela educação dos estudantes com deficiência, transtornos globais de desenvolvimento, altas habilidades/superdotação; d) os programas Sala de Recursos Multifuncionais (SRM) e Escola Acessível (EA) não são referenciados como programas que integram as Políticas Educacionais na Perspectiva da Inclusão; e e) o gestor escolar é responsável pela articulação democrática da escola, pelos recursos humanos e financeiros. Num contexto com poucos recursos a Educação Inclusiva nas escolas analisadas encontra-se ameaçada. As políticas educacionais, na perspectiva da inclusão, resultam da influência dos mecanismos internacionais e da organização da sociedade civil. No contexto da prática (escola), esses documentos orientam as ações desenvolvidas pelos gestores escolares que, ao interpretá-los, omitem ou desconhecem aspectos importantes que visam garantir o acesso e a permanência do estudante público-alvo da Educação Especial na escola regular.
Keywords: Educação e Estado - Rio Grande do Sul; Escolas públicas - Administração; Integração social; Education and state - Rio Grande do Sul (Brazil); Public Schools - Administration; Social integration